Derivative and Simultaneous Equation Methods for the Determination of Fluorometholone and Ketorolac in Ophthalmic Preparations - Kumar, Chandaka Prasanna (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: Two new spectrophotometric techniques have been developed for the quantification of Fluorometholone and Ketorolac tromethamine in eye drops. Materials and Methods: First derivative method and simultaneous equation method were developed for the determination of Fluorometholone and Ketorolac tromethamine in both sodium acetate buffer (pH 4.0) and phosphate buffer (pH 4.0) reagent solutions. Results and Discussion: Fluorometholone and Ketorolac tromethamine has followed linearity over the concentration range 1-20 Î¼g/mL sodium acetate buffer (pH 4.0) and 2-30 Î¼g/mL in phosphate buffer. Conclusion: The methods were validated and applied for the simultaneous determination of Fluorometholone and Ketorolac tromethamine in the available ophthalmic preparations